Subarachnoid Hemorrhage-Induced Hydrocephalus in Rats - Okubo, Shuichi (2012)
BACKGROUND AND PURPOSE: Hydrocephalus is an important complication of subarachnoid hemorrhage (SAH). We investigated the occurrence of acute hydrocephalus in a rat SAH model. METHODS: SAH was induced by endovascular perforation in adult male Sprague-Dawley rats (n=36). Sham rats (n=8) underwent the same procedure without perforation. MRI was performed 24 hours after SAH and the volume of the ventricular system and extent of T2* hypointensity lesions were measured. We defined hydrocephalus as ventricular volume greater than +3 standard deviations above the mean in sham animals. SAH grade was determined and brains were used for histology, immunohistochemistry, Perls’ staining and Western blot analysis. Ventricular wall damage was defined as percentage of ependymal surface disruption. RESULTS: All surviving rats (n=27) after SAH had ventricular enlargement (33.6±4.7 vs. 13.5±1.4 mm(3) in sham animals, p<0.01). Ventricular volume correlated with SAH severity (r=0.48, p<0.05). 12 of 27 SAH rats demonstrated hydrocephalus and all had intraventricular blood accumulation. Rats with hydrocephalus had more severe ventricular wall damage (7.4±1.2%) than the sham animals (0.6±0.2%, p<0.01) and rats without hydrocephalus (1.1±0.2%, p<0.01). Periventricular iron deposition was observed and HO-1 and Iba-1 expression were markedly increased in hydrocephalus rats. CONCLUSIONS: SAH causes ventricular enlargement in a rat endovascular perforation model, with hydrocephalus occurring in 44% of animals at 24 hours. Rats with hydrocephalus had more severe SAH, intraventricular hemorrhage and greater ventricular wall damage.